Komisi Penyiaran Indonesia Daerah: Peran Kontrol Dan Tantangannya Sebagai Lembaga Regulator Penyiaran - Riana, Nina Ivy (Universitas Brawijaya, 2023)
Indonesia as a democratic country guarantees the rights of citizens to produce as well as obtain information in accordance to Undang-Undang Dasar Tahun 1945 article 28 F. There is Undang-undang 32 Tahun 2002 Tentang Penyiaran which is equipped with a regulatory agency (Komisi Penyiaran Indonesia) to guarantee these rights. This research looks further at the control role and challenges faced by Regulatory Agencies at the regional level with data sources originating from the Komisi penyiaran Indonesia daerah in the East Kalimantan Province operating in the Samarinda City area, furthermore this research includes the study of Communication law and policy, especially in the field of the federal communications commission and broadcast policy-making which was adapted into a study of the regional Indonesian Broadcasting Commission and broadcasting policy. This phenomenon is seen from an interpretive point of view with a descriptive qualitative approach, the results of this research show that the control role of KPID of East Kalimantan Province on the broadcasting industry in Samarinda City is not optimal and tends to be weak due to structural and cultural barriers.